PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL DI KABUPATEN TEMANGGUNG - Ritriani Ika Wulansari; Suwanto Adhi; Rina Martini (Journal of Politic and Government Studies, 2015)
Already from the first, the government is already taking action and efforts in thehealth sector is to provide health insurance for all citizens of Indonesia. Based on article 5 ofLaw No. 36 of 2009 on Health, explained that everyone has an equal right to have access toresources in the health sector. Therefore, dated January 1, 2014 the government in the SocialSecurity Agency (BPJS) Health implement policies to ensure the health of every citizen in theform of National Health Insurance (JKN).In this study focused on the implementation of the National Health Insurance inTemanggung District. This study was conducted to determine how far the implementation ofJKN in Temangggung and what are the obstacles and complaints in the implementation ofthis JKN. The method used is descriptive qualitative. Sources of primary data obtainedthrough interviews with a purposive sample system (taking intentionally) to obtain keyinformants (people who know the correct and reliable), while secondary data sourcesobtained from documents, archives, and other sources related to the research. Analysistechniques using triangulation techniques, performed with test information with fieldobservations, as well as to confirm to infroman and other sources.From the results it can be seen that in the course of one year policy, it can cover 45%of residents in the Temanggung District. In addition, there are many complaints that arise inthe community as not know where FKTP where registered participants, participants were notgiven the maximum service due to the number of patients who exploded, drugs givenstandard, the existence of an early return from a claim that has been discharged, etc. From thegiver services complained continuous regulatory changes occur, and a lack of coordination ofthe executive (BPJS) and service providers (FKTP). On the other hand, there are still manypoor people who are not covered by JKN as PBI participants. As well as the mostfundamental thing is the lack of awareness of the importance of community health insuranceand also many who still objected to the specified monthly fee.Should the enforcement of strict regulations so that the passage of health care can be amaximum again and also so that people can be aware that health insurance is important.Hopefully, the realization of the expectations of the public in 2019 all Indonesian citizenswithout exception has been a member of membership BPJS Health.Keywords: public health services, National Health Insurance, BPJS.